Solution of Some Diophantine Problems: Exploring the History and Integer Solution of Diophantine Equations (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In this paper we shall study on the some famed history and integer solution of some Diophantine Equations in +ve integer solution and connection with Pythagorean triples and Pell’s Equation. We have shown that how some solution can be found with the help of conversion into Diophantine equation.